PARTISIPASI MASYARAKAT DALAM PEMBANGUNAN DI PEDESAAN Telaahan atas tulisan David C. Korten - Susantyo, Badrun (Sosio Informa, 2007)
Participation is like a small coin, one side to assume the shape of participation with their whole and the other side to show the spirit of participation. Community participation are a develop paradigm to focusing the involved of community, beginning from planning. Community participation has an opportunity to influence the policy of development, to answered what the people needed. Through the participation, people knowing their problem and how to solved. Besides it, they have resources to improved their live good. Key words : Participation, local community, rural development.